Lärares (digitala) kompetens före, under och efter covid-19: Skärvor av förståelse från skolor i Sverige - Stenliden, Linnéa; Martín Bylund, Anna; Landkvist, Lena; Ekström Lind, Linda; Kellgren Lundberg, Susanna; Stenmark, Hannes; Wilhelmsson, Cornelia (Utbildning & Lärande, 2021)
This study chrono-logically investigates teachers’ professional knowledge in relation to the digitally ‘boosted’ educational landscape caused by the Covid-19-pandemic. The aim is to describe how teachers employ their competences under extreme digitized circumstances by reading these through the lens of ordinary, to greater extent analogically organized schooling. The study is inspired by action research and data is collected in schools by five secondary and upper secondary teachers between March 19 and April 2, 2020. The analysis highlights qualitative aspects of teachers’ (digital) competence when teaching is affected by digital “interferences” in its corporeal and material framing, a dissolved spatiality and “truncated” senses/sensuousness. Employing different dimensions of knowledge in terms of intellectus and ratio, the study argues that subjective, emotional and relational processes of teachers’ digital competence need to be prioritized in contrast to the easily measurable aspects that tend to overrun the discussions about educational digitalization and its knowledge in society.